Doctor Thorne - Trollope, Anthony, 1815-1882 (Trollope, Anthony, 1815-1882. Chronicles of Barsetshire., 2016)
The breathtaking love story of an illegitimate girl and the young noble who would choose her above all. Gender issues and economic hardships are dealt with deftly in Doctor Thorne, the third novel in the Chronicles of Barsetshire, and arguably the saga's finest love story. Set in rural England in the fictitious county of Barsetshire, this Victorian novel is one of Anthony Trollope's most optimistic and engaging works. When Henry Thorne seduces local villager Mary Scatcherd, her stonemason brother, Roger, avenges the indignity by murdering Thorne in cold blood. While Roger goes off to prison, Mary follows a promising suitor to the Americas, leaving her illegitimate daughter in the hands of Dr. Thomas Thorne, brother to her murdered lover. The physician names the girl Mary, after her mother, and in an effort to protect the girl's reputation-and keep her away from her murderous uncle-he keeps her lineage a secret. Later, when young Mary falls in love with the heir of the squire of Greshamsbury, the lad is put in the precarious position of pursuing the girl despite his family's clear desire for him to marry a woman with titles and a much better financial standing. Doctor Thorne is one of the most lighthearted and hopeful tales by Trollope. Addressing the flaws inherent in the social mores of his day, the author, a master of the English novel, entreats readers to consider-as his characters must-profound issues of life, love, and morality. This ebook has been professionally proofread to ensure accuracy and readability on all devices.